Adopt or Innovate: Understanding Technological Responses to Cap-and-Trade - Raphael Calel (Center for Economic Studies and ifo Institute (CESifo), 2018)
Environmental regulations have consistently been found to spur innovation in `clean' technologies, with one significant exception. Past cap-and-trade programs have encouraged adoption of existing pollution control technologies, but had little effect on innovation. Several explanations have been offered, including secondary market failures and a lack of polluter sophistication. In this paper I argue that it likely has more to do with the state of the technologies. Using a newly constructed panel of British companies, I show that the European carbon market - the world's largest cap-and-trade program - has, contrary to past experience, encouraged innovation rather than adoption. I discuss how these contrasting findings can be reconciled, and the implications for planned reforms.
Keywords: O30; Q55; Q58; 330; EU emissions trading system; induced innovation; directed technological change; technology diffusion